PERANCANGAN WEBSITE COMPANY PROFILE PT COLUMBUS BERBASIS RESPONSIF UNTUK MENINGKATKAN BRANDING PERUSAHAAN - Anugrah , Aldof Faris; Abdurahman, Dede (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The development of digital technology requires companies to have online media that can strengthen their image and competitiveness. PT Columbus, which operates in the electronic furniture sector, faces challenges because its website is still static and not very responsive. This study aims to design and implement a responsive company profile website using the Waterfall system development method which includes needs analysis, design, implementation, testing, and maintenance. The technologies used are HTML, CSS, JavaScript, Bootstrap, PHP Native, and MySQL, supported by XAMPP, Visual Studio Code, and cloud-based hosting. The results of the study produced a website with key features such as a company profile, products, gallery, contact, and admin panel that is proven to be responsive, secure, and easily accessible on various devices. This implementation is able to improve company branding through a professional appearance, intuitive navigation, and more effective information delivery so as to strengthen relationships with customers and expand PT Columbus's market reach in the era of global competition.